1966
DOI: 10.1021/ic50037a040
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Circular Dichroism for Tetrachloroplatinate(II) Ion

Abstract: NOTES 491were found to be monomeric and both exhibited normal magnetic moments. The visible spectrum of the anhydrous material in carbon tetrachloride, Figure 1, shows a well-separated shoulder on the high-energy side of the visible band; the spectrum of the dihydrate in the same solvent shows a less pronounced shoulder much closer to the main band. Since a well-separated shoulder is present on the high-energy side of the main band in the spectra of all other 6-dicarbonyl complexes of copper(II), this shoulder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1968
1968
1984
1984

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Martin, Foss et al (20) found such an A-term at 30,300 cm ^ in the MCD spectrum of a K^PtCl^ solution. Thus, the absorption peak appearing in both polarizations of the crystal spectra at about 29,500>…”
Section: -mentioning
confidence: 95%
See 1 more Smart Citation
“…Martin, Foss et al (20) found such an A-term at 30,300 cm ^ in the MCD spectrum of a K^PtCl^ solution. Thus, the absorption peak appearing in both polarizations of the crystal spectra at about 29,500>…”
Section: -mentioning
confidence: 95%
“…The Magnetic Circular Dichroism spectrum for PtCl^ (20,21) permitted the unambiguous assignment of the •>-transition.…”
Section: -mentioning
confidence: 99%
“…McCarviiIc (7,8) Ttic CD attachment for the Jasco was used for the data in Table 3 Both instruments were calibrated with a 1 mc/ml solution of …”
Section: Opticil Rotatory Dispersionmentioning
confidence: 99%
“…1) high-quality polarized absorption spectra for single crystals of KgPtCl^ were obtained by Martin et al (19) at both room temperature 2-and 15K, and 2) Magnetic Circular Dichroism (MCD) spectra for PtCl^ were obtained by Martin, Foss et al (20) and McCaffrey, Schatz, and Stephens (21).…”
Section: Xz Yzmentioning
confidence: 99%